2006
DOI: 10.1111/j.1528-1167.2006.00554.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Predictors of Seizures in Patients with Alzheimer's Disease

Abstract: Summary: Purpose: To determine cumulative incidence and predictors of new-onset seizures in mild Alzheimer's disease (AD) with a cohort followed prospectively. Limited information is available on the incidence of seizures, and no reports exist of seizure predictors in AD patients.Methods: Mild AD patients were prospectively followed at 6-month intervals to estimate incidence of unprovoked seizures, compare age-specific risk of unprovoked seizures with population norms, and identify characteristics at baseline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
428
7
11

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 524 publications
(483 citation statements)
references
References 18 publications
37
428
7
11
Order By: Relevance
“…Gliosis is prominent in Alzheimer's disease, but the incidence of seizure is only moderately increased compared with reference populations (Hauser et al, 1986;Unger, 1998;Amatniek et al, 2006). Interestingly, a recent report has revealed that some mouse models of Alzheimer's disease (hAPPJ20) have nonconvulsive seizures and compensatory inhibitory changes in hippocampal circuitry (Palop et al, 2007).…”
Section: Reactive Astrocytes In a Mouse Model Of Alzheimer's Diseasementioning
confidence: 99%
“…Gliosis is prominent in Alzheimer's disease, but the incidence of seizure is only moderately increased compared with reference populations (Hauser et al, 1986;Unger, 1998;Amatniek et al, 2006). Interestingly, a recent report has revealed that some mouse models of Alzheimer's disease (hAPPJ20) have nonconvulsive seizures and compensatory inhibitory changes in hippocampal circuitry (Palop et al, 2007).…”
Section: Reactive Astrocytes In a Mouse Model Of Alzheimer's Diseasementioning
confidence: 99%
“…31 This is correlated with increased epileptic seizures in AD patients. 32 In addition, the risk of epileptic activity is 87-fold greater in AD patients with early-onset dementia (that is typically characterized by Aβ pathology) and the relationship between AD and seizures is even tighter in early-onset familial AD 33,34 (the 3xTg-AD mouse model perhaps resembles early-onset familial AD better than late onset AD, as it has genetic mutations from birth). These results raise an important question of whether the extent of subclinical epileptic activity in AD has been underestimated.…”
Section: Effect Of Lipoic Acidmentioning
confidence: 99%
“…Furthermore, the incidence has been shown to increase with age in the Nordic population [21][22][23]. The reported prevalence of EP in dementia and AD varied from 5% to 64% [24][25][26][27][28][29][30][31][32][33][34]. When all cognitively unimpaired subjects with HS were lumped together here, three out of 23 (11%) had displayed EP during life, thus indicating a high frequency, when compared to the general population.…”
Section: Discussionmentioning
confidence: 98%